Hubungan Lama Terpasang Infus dengan Kualitas Tidur Anak di Rawat Inap Rumah Sakit Umum Daerah Kota Depok - Tatiana Siregar; Auliya Risha (Jurnal Persada Husada Indonesia, 2018)
Children who experience hospitalization and receive invasive procedures in the form of infusion, in addition to causing physical disorders such as pain, can also affect the psychological. In addition, the aspect that has not received enough attention is the fulfillment of the quality of rest or sleep of children. The study aims to analyze the quality of sleep of children when attached to an IV during treatment at Regional Public Hospital, Depok City. Quantitative research design with cross approach, Chi Square data analysis on 60 school-age children with the Purposive Sampling method. The results show a p value of 0.734> α (95% CI) means that there is no relationship between the duration of infusion and the sleep quality of school-age children, with an OR value of 1.429, meaning that children who have long-term infusion have a 1,429 times chance of poor sleep quality compared with long duration of short term infusion, but because 95% CI includes the number 1 variable long time long term infusion is not necessarily a risk factor for poor sleep quality. It is recommended to nurses to pay more attention to factors that can result in a lack of fulfillment of a child's sleep quality when in hospital, so that the child's sleep quality can be met.